Isoflavone and Antioxidant of Instant Cream Soup Made from Pumpkin and Tempeh and Their Active Compound in Ovariohysterectomy Rat-Induced Alzheimer’s Disease - Budi Setiawan; Salma S. Aulia; Ahmad Sulaeman; Clara M. Kusharto; Ekowati Handharyani (International Journal of Food Science)
Menopause period associated with brain function disorders can caused by decreasing estradiol levels and increasing oxidative stress in the body. Antioxidant agents are required to balance oxidative stress in the body. Instant cream soup made from pumpkin and tempeh is a supplementary food containing isoflavone and antioxidant agents. This study is aimed at analyzing the content of antioxidant level and isoflavones (genistein and daidzein) in instant cream soup and their effect on ovariohysterectomy (OVx) rats. Instant pumpkin cream soup with and without tempeh were subjected to isoflavone content and antioxidant analysis. Serum estradiol was analyzed using enzyme-linked immunosorbent assay. Liver concentration of malondialdehyde (MDA) and activities of superoxide dismutase (SOD) were measured by spectrophotometric methods. The study showed that the isoflavone content (genistein 370.86 g/100 g, daidzein 185.61 g/100 g) was only present in the pumpkin instant cream soup with tempeh (IPTS). IPTS has higher antioxidant levels (134.25 mg AEAC/100 g) than instant pumpkin cream soup without tempeh (IPS). In vivo study, experimental rats showed that OVx increased malondialdehyde (MDA) levels up to 5.85-6.07 nmol mL-1 as compared to control (4.47 nmol mL-1). Moreover, instant pumpkin cream soup with tempeh treatments significantly increased serum estradiol levels (2.37–3.63 μg) and superoxide dismutase (SOD) levels of 497.49-558.89 U mL-1. This study concluded that instant pumpkin cream soup and tempeh contained isoflavone and antioxidant, and it increased estradiol serum and SOD level.